ANALISA SISTEM PENGAMAN DAN KEMAMPUAN HANTAR ARUS MOTOR PADA MESIN OTOMATIS PENGERING GABAH - Gellen Twin Agiantoro; Moh Toni Prasetyo (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2018)
The purpose of the Protector System in electric motor on the Automatic Rice Dryer Machine to control the motor performance in order to work optimally. The protector system was calculated by current load through the electrical motor  and then converted to  calculate current  driving  system.  The current driving system in each electrical motor is different because it is affected by the motor specification. The benefit to understand it is to prevent the damage on the electrical motor cause the coil wire burned down by over current. The motor on each of the Automatic Rice Dryer Machine has its own function so the machine works in structured mode with automatic control. As a result, the machine is suitable to used by farmers to dry the rice, so they were not worried about the weather. Furthermore, they can dry the rice without large areas and sunshine. Keywords: Protector, System, Current, Motor, Automatic